Design and Control Strategies of Multirotors with Horizontal Thrust-Vectored Propellers - Ricardo Rosales Martinez; Hannibal Paul; Kazuhiro Shimonomura (Drones)
With the growing adoption of Unmanned Aerial Vehicles (UAVs) in industrial and commercial sectors, the limitations of traditional under-actuated multirotors are becoming increasingly evident, particularly in manipulation tasks. Limited control over the thrust vector direction of the propellers, coupled with its interdependence on the vehicle’s roll, pitch, and yaw moments, significantly restricts manipulation capabilities. To address these challenges, this work presents a control framework for multirotor UAVs equipped with thrust-vectoring components, enabling enhanced control over the direction of lateral forces. The framework supports various actuator configurations by integrating fixed vertical propellers with horizontally mounted thrust-vectoring components. It is capable of handling horizontal thruster setups that generate forces in all directions along the x- and y-axes. Alternatively, it accommodates constrained configurations where the vehicle is limited to generating force in a single direction along either the x- or y-axis. The supported UAVs can follow transmitter commands, setpoints, or predefined trajectories, while the flight controller autonomously manages the propellers and thrusters to achieve the desired motion. Moment evaluations were conducted to assess the torsional capabilities of the vehicles by varying the angles of the thrusters during torsional tasks. The results demonstrate comparable torsional magnitudes to previously studied thrust-vectoring UAVs. Simulations with vehicles of varying inertia and dimensions showed that, even with large horizontal thruster offsets, the vehicles followed desired trajectories while maintaining stable horizontal orientation and smaller attitude variations compared to normal flight. Similar performance was observed with positive and negative vertical offsets, demonstrating the framework’s tolerance for thrusters outside the horizontal plane.